Counseling the hard cases : true stories illustrating the sufficiency of God's resources in Scripture - Scott, Stuart, 1955-; Lambert, Heath, 1979- (Nashville, Tenn. : B & H Academic, 2012)
"Biblical counselors have worked for decades to demonstrate that God's resources in Scripture are sufficient to help people with their counseling-related problems. In Counseling the Hard Cases, editors Stuart Scott and Heath Lambert use the true stories of real patients to show how the truths of God's Word can be released to bring help, hope, and healing into the lives of those who struggle with some of the most difficult psychiatric diagnoses. From pastors and academics to physicians and psychiatrists, a world-class team of contributing counselors share accounts of Scripture having helped overcome bipolar, dissociative identity, and obsessive compulsive disorders, postpartum depression, panic attacks, addiction, issues from childhood sexual abuse, homosexuality, and more. The book also shows how the graces of Christ, as revealed in the Bible, brought powerful spiritual change to the lives of such people who seemed previously burdened beyond hope by mental and emotional roadblocks. Contributors include John Babler, Ph.D., Kevin Carson, D.Min., Laura Hendrickson, M.D., Garrett Higbee, Psy.D., Robert Jones, D.Min., Martha Peace, RN, Steve Viars, D.Min., and Dan Wickert, M.D." -- Publisher description.
Introduction: The sufficiency of Scripture, the biblical counseling movement, and the purpose of this book / Heath Lambert -- "Mariana" and surviving sexual abuse / Laura Hendrickson -- "Brian" and obsessive-compulsive disorder / Steve Viars -- "Sarah" and postpartum depression / Heath Lambert -- "Mary" and paralyzing fear / Dan Wickert -- "Ashley" and anorexia / Martha Peace -- "Tony" and bipolar disorder / Garrett Higbee -- "Jackie" and dissociative identity disorder / Stuart Scott -- "Jason" and homosexuality / Kevin Carson -- "Julie" and addictions and adultery / Robert D. Jones -- "Jennifer" and an apparent hard case / John Babler -- Concluding reflections / Heath Lambert and Stuart Scott.
Includes bibliographical references and index.
Keywords: Pastoral counseling